KAJIAN PENINGKATAN PERANAN TRANSPORTASI MULTIMODA DALAM MEWUJUDKAN VISI LOGISTIK INDONESIA 2025 - Tulus Irpan H S; Imam Sony; Sarinah Sarinah (Institut Transportasi dan Logistik Trisakti, 2016)
In the last 10 years, the practice of logistics in the industry changing very remarkable. Global competition in the market of products and services to encourage the diversity of products to meet the needs of market segments are also diverse, high standard of product quality, timely delivery of goods is very dependent on the condition of public infrastructure provided by the government of a country. As a result, the demands of efficiency in higher logistics activities, including the level of security quality, safety and service. The lack of infrastructure support and the absence of